Corn texture and particle size in broiler diets - Benedetti, M P [UNESP]; Sartori, José Roberto [UNESP]; Carvalho, F B [UNESP]; Pereira, L A [UNESP]; Fascina, V B [UNESP]; Stradiotti, A C [UNESP]; Pezzato, Antonio Celso [UNESP]; Costa, Ciniro [UNESP]; Ferreira, J G [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2011)
The objective of this study was to evaluate the effect of corn texture and the particle size on broiler performance, carcass yield, nutrient digestibility, and digestive organ morphometrics. In Experiment I, 720 male Cobb chicks were distributed in a completely randomized experimental design with a 2 x 3 factorial arrangement, consisting two corn textures (dented and hard) and three corn particle sizes, was applied, with four replicates of 30 birds each. Corn particle size was classified according to geometric mean diameter (GMD) as fine - 0.46 mm; medium - 0.73 mm, and coarse - 0.87 mm. In Experiment II, 120 broiler chicks were used to evaluate corn digestibility during the periods of 16 to 22 days and 35 to 41 days of age, using the method of total excreta collection. In Experiment I, corn particle size influenced body weight, average weight gain, feed intake and feed conversion ratio of 21-day-old birds. Corn texture and particle size did not affect the performance of 42-day-old broilers or carcass traits. In Experiment II, there was no influence of corn texture and particle size on digestive organ weights. Dented corn increased nitrogen excretion in the first trial, and hard corn improved dry matter digestibility in the second metabolic trial. Corn with fine particle size promotes better performance of broilers at 21 days of age. Hard corn results in higher dry matter digestibility and lower nitrogen excretion, and consequently higher production factor in 42-day-old broilers.
Keywords: Carcass traits; digestibility; GMD; particle size; performance